Mapping the Consequences of Impaired Synaptic Plasticity in Schizophrenia through Development: An Integrative Model for Diverse Clinical Features. Issue 10 (October 2017) - Forsyth, Jennifer K.; Lewis, David A.
Abstract : Schizophrenia is associated with alterations in sensory, motor, and cognitive functions that emerge before psychosis onset; identifying pathogenic processes that can account for this multi-faceted phenotype remains a challenge. Accumulating evidence suggests that synaptic plasticity is impaired in schizophrenia. Given the role of synaptic plasticity in learning, memory, and neural circuit maturation, impaired plasticity may underlie many features of the schizophrenia syndrome. Here, we summarize the neurobiology of synaptic plasticity, review evidence that plasticity is impaired in schizophrenia, and explore a framework in which impaired synaptic plasticity interacts with brain maturation to yield the emergence of sensory, motor, cognitive, and psychotic features at different times during development in schizophrenia. Key gaps in the literature and future directions for testing this framework are discussed. Trends: The broad phenotype of schizophrenia includes sensory, motor, and cognitive signs and symptoms that emerge before psychosis. Evidence from post-mortem and large-scale genetic studies suggests that synaptic plasticity is disrupted in schizophrenia and may be a key pathogenic factor in the disease. Given the role of synaptic plasticity in learning, memory, and the maturation of neural circuits, the consequences of impaired plasticity through development may explain the emergence of many signs and symptoms of the broader schizophrenia phenotype. The extant literature is consistent with manifestations of impaired synaptic plasticity that may be detectable as early and fundamental deficits in learning and memory, and the progressive emergence of broader sensory, motor, cognitive, and psychotic features.